Determining universal processes related to best outcome in emergency abdominal surgery: a multicentre, international, prospective cohort study. Issue 10 (29th October 2014) - Bhangu, Aneel; Fitzgerald, J Edward; Fergusson, Stuart; Khatri, Chetan; Holmer, Hampus; Søreide, Kjetil; Harrison, Ewen M
Abstract : Introduction: Emergency abdominal surgery outcomes represent an internationally important marker of healthcare quality and capacity. In this study, a novel approach to investigating global surgical outcomes is proposed, involving collaborative methodology using 'snapshot' clinical data collection over a 2-week period. The primary aim is to identify internationally relevant, modifiable surgical practices (in terms of modifiable process, equipment and clinical management) associated with best care for emergency abdominal surgery. Methods and analysis: This is a multicentre, international, prospective cohort study. Any hospital in the world performing acute surgery can participate, and any patient undergoing emergency intraperitoneal surgery is eligible to enter the study. Centres will collect observational data on patients for a 14-day period during a 5-month window and required data points will be limited to ensure practicality for collaborators collecting data. The primary outcome measure is the 24 h perioperative mortality, with 30-day perioperative mortality as a secondary outcome measure. During registration, participants will undertake a survey of available resources and capacity based on the WHO Tool for Situational Analysis. Ethics and dissemination: The study will not affect clinical care and has therefore been classified as an audit by the South East Scotland Research Ethics Service in Edinburgh, Scotland. Baseline outcome measurement in relation to emergency abdominal surgery has not yet been undertaken at an international level and will provide a useful indicator of surgical capacity and the modifiable factors that influence this. This novel methodological approach will facilitate delivery of a multicentre study at a global level, in addition to building international audit and research capacity. Trial registration number: The study has been registered with ClinicalTrials.gov (Identifier: NCT02179112 ).